2020
DOI: 10.1093/neuros/nyaa110
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Low-Profiled Visualized Intraluminal Support Stent-Assisted Coiling and Coiling Only for Acutely Ruptured Intracranial Aneurysms: Safety and Efficacy Based on a Propensity Score-Matched Cohort Study

Abstract: BACKGROUND Low-profiled visualized intraluminal support (LVIS) is suggested as a promising stent for complex intracranial aneurysms. However, the safety and efficacy of LVIS-assisted coiling of acutely ruptured wide-necked intracranial aneurysms have not been well reported. OBJECTIVE To evaluate the safety and efficacy of LVIS-assisted coiling of acutely ruptured wide-necked intracranial aneurysms compared with contemporary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Multivariate regression analysis showed that coiling without stents was the only factor significantly associated with aneurysm recurrence. Other studies also reported that SAC embolization significantly reduced the recurrence and retreatment rates of aneurysms ( 14 , 18 , 19 ). In this study, a total of 105 patients who received DSA were followed.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Multivariate regression analysis showed that coiling without stents was the only factor significantly associated with aneurysm recurrence. Other studies also reported that SAC embolization significantly reduced the recurrence and retreatment rates of aneurysms ( 14 , 18 , 19 ). In this study, a total of 105 patients who received DSA were followed.…”
Section: Discussionmentioning
confidence: 82%
“…Roh et al ( 13 ) reported that the rate of thromboembolic complications in stent-assisted coil embolization of ruptured intracranial aneurysms was approximately twice as high as that in non-stent coil embolization, and external ventricular drainage-related re-hemorrhage was approximately five times higher than that of non-stent coil embolization. However, Xue et al ( 14 ) compared the outcomes of acute ruptured intracranial aneurysms treated with low-profile visualized intraluminal support SAC or CA and found no significant difference in the overall incidence of complications between the two groups (7.2 vs. 4.3%, P = 0.207). In our study, univariate analysis showed that there was no significant risk factor for the overall perioperative procedure-related complications, including hemorrhagic complications and ischemic complications.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 56 studies comprising 4,373 patients harboring 4,540 aneurysms were included ( 6 , 13 67 ). Patients were divided into two groups on the basis of stent type: laser-cut stents (2,076 aneurysms in 1991 patients; mean follow-up, 12.99 months) and braided stents (2,464 aneurysms in 2,382 patients; mean follow-up, 18.41 months).…”
Section: Resultsmentioning
confidence: 99%
“…With the advances in neuroimaging and endovascular devices, several recent studies corroborated comparable effectiveness and better prognosis when using endovascular treatment as compared to microsurgical clipping (5,6) for ruptured tiny intracranial aneurysms. Simultaneously, previous studies indicated that the stent-assisted coiling (SAC) technique was associated with a higher complete occlusion rate and lower recurrence rate at follow-up compared with coiling alone (CA) in ruptured intracranial aneurysms (7,8). However, studies on aneurysm occlusion, recurrence, and procedural complication rates of SAC treatment for ruptured tiny intracranial aneurysms were limited and heterogeneous (9, 10).…”
Section: Introductionmentioning
confidence: 99%